“Propuesta de un sistema de gestión de residuos sólidos en el camal Tecnológico del Cantón Saquisili Provincia de Cotopaxi”. - Yanchapaxi Hidalgo, Daysi Guillermina (2023)
The present research work is aimed at developing a solid waste management system for the Saquisili canton's technological farm, which allows in the first instance to determine the environmental problems that trigger social, cultural and economic problems in order to develop a proposal based on field visits that allowed to optimize and potentiate solid waste management. The methodology used for the construction of this work has a qualitative-descriptive approach. descriptive approach, under these factors the objectives were developed, such as the analysis of the current state of the waste management system and how the slaughtering process generates environmental impacts under the application of an environmental impact matrix, as well as the quantification of waste generation carried out under the follow-up method, which allowed determining the environmental impact of the process. The quantification of waste generation carried out under the follow-up method allowed determining the per capita production of waste generated by the slaughtering process for cattle, which is 33/kg/animal/day, and for sheep, which is 12/kg/animal/day, the per capita production of inorganic waste is in the range of 3. In this way, the research is linked to the reduction of waste with new alternatives for the use of the Integral Management Model, which is directed to the administrative and operational personnel of the slaughterhouse and consists of 4 lines of action, each with its own program and activities. At the conclusion of the research, it can be determined that it will be a tool that will allow the implementation of alternatives for the use of waste, thus improving the management and final disposal, thus improving the operation of the technological slaughterhouse.